Public Support Dynamics Toward the Discourse of Muhammadiyah Islamic Bank Establishment in West Kalimantan - Nurfadzri, Muhammad; Anwari, Muhammad Khairul; Anshori, Aiyub (Universitas Muhammadiyah Pontianak, 2024)
This study aims to examine the internal and external perceptions of the Muslim community in West Kalimantan regarding the discourse on establishing Bank Syariah Muhammadiyah. The research is motivated by extensive discussions surrounding Muhammadiyah’s plan to establish a bank, considering the organization’s significant economic potential and its existing financial ecosystem. A descriptive quantitative approach was employed, utilizing a survey method through questionnaires, and data analysis was conducted using SmartPLS. The study population comprised Muslims in West Kalimantan, with a sample of 75 respondents selected through purposive sampling. The analysis included outer model testing (construct validity and reliability) and inner model testing to assess the influence of each independent variable on the dependent variable. The findings reveal that internal perceptions have a positive and significant effect on the intention to support the establishment of Bank Syariah Muhammadiyah (β = 0.535; f² = 0.442, large effect size). External perceptions also show a positive and significant influence (β = 0.308; f² = 0.146, medium effect size). The coefficient of determination (R² = 0.572) indicates that 57.2% of the variance in the discourse on bank establishment is explained by these two perception variables.